2009
DOI: 10.1371/journal.pgen.1000437
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Toxin–Antitoxin Systems: More Than Selfish Entities?

Abstract: Bacterial toxin–antitoxin (TA) systems are diverse and widespread in the prokaryotic kingdom. They are composed of closely linked genes encoding a stable toxin that can harm the host cell and its cognate labile antitoxin, which protects the host from the toxin's deleterious effect. TA systems are thought to invade bacterial genomes through horizontal gene transfer. Some TA systems might behave as selfish elements and favour their own maintenance at the expense of their host. As a consequence, they may contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
400
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(407 citation statements)
references
References 59 publications
3
400
0
Order By: Relevance
“…However, the potential risk of underestimation of the prevalence of TA loci in the clinical E. coli isolates must be taken into consideration due to sequence variations of either toxin or antitoxin genes at primer annealing sites, and/or diverse configurations of the genes in bacterial genomes (Van Melderen & Saavedra De Bast, 2009;Leplae et al, 2011). To date, only Norton & Mulvey (2012) have observed that uropathogenic B2 coli genome, and the order of rings/genomes in E. coli phylogroups, starting from the innermost one, was included in Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential risk of underestimation of the prevalence of TA loci in the clinical E. coli isolates must be taken into consideration due to sequence variations of either toxin or antitoxin genes at primer annealing sites, and/or diverse configurations of the genes in bacterial genomes (Van Melderen & Saavedra De Bast, 2009;Leplae et al, 2011). To date, only Norton & Mulvey (2012) have observed that uropathogenic B2 coli genome, and the order of rings/genomes in E. coli phylogroups, starting from the innermost one, was included in Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…An indirect mechanism was proposed in the case of the prevention of plasmid establishment (50). According to this model, a host cell harboring a chromosomally encoded antitoxin would neutralize the toxin of a plasmid-encoded T-A system and prevent plasmid addiction (50).…”
Section: Non-r-m Defense Systemsmentioning
confidence: 99%
“…For the chromosomal ccd systems, these include the antiaddiction model (11), which states that the chromosomally encoded ccd system (ccd Ech ) protects the cell against postsegregational killing mediated by its F-plasmid ccd (ccd F ) homolog, whereas for the ccd O157 system, it has been suggested that this system is devoid of any biological role in the E. coli species (12). Models proposed for other chromosomal TA systems include the programmed cell death (PCD) model, the growth modulation model, the persistence model, and the development model (13). TA loci have been proposed as general stress response elements in prokaryotes (14)(15)(16)(17).…”
Section: Abstract Toxin-antitoxin Persistencementioning
confidence: 99%